La place de la grammaire dans l’enseignement du français langue étrangère dans le cycle secondaire en Algérie - Hammouche, Sarra (Journal of Human Sciences, 2017)
In this article, we have brought to light the place reserved to grammar in the FLE teaching in the secondary cycle. In effect, we analyzed guides, accompanying documents, programs and manuals of the three levels what allowed us to make a number of remarks. These bring us to say that grammatical difficulties facing the learners are partly due to the tiny place that occupies grammar in the secondary cycle and to the multiple theories that underlie it.